Intragenic deletion mutation in the gene desmoglein 4 underlies autosomal recessive hypotrichosis in six consanguineous families. Issue 3 (June 2016) - Muhammad, Dost; Khan, Bushra; Raza, Syed I.; Ahmad, Farooq; Channa, Naseem A.; Ansar, Muhammad; Ahmad, Wasim; Basit, Sulman
ملخص: الأهداف: نقص الشعر الجسمي الموضعي المتنحي هو اضطراب فقدان الشعر البشري غير المتلازمة، التي تؤثر على فروة الرأس والحاجبين والرموش، وأجزاء أخرى من الجسم . ستة عوائل مصابين( بحيث كل عائلة فيما بينهم صلة قرابة ) بهذا النوع من الاضطراب تساقط الشعر وقد تم التحقيق على المستويين السريرية والجزيئية. الطريقة: تم اختبار الربط في ستة عوائل مع فرد مصاب واحد من كل عائلة بواسطة التنميط الجيني علامة الميكروستلايت مرتبطة بمواضع نقص الشعر الجسمية المتنحية بما في ذلك نقص الشعر الجسمي الموضعي المتنحي(LAH) ١،٢ و ٣. تم إجراء تحليل تسلسل مواقع الترميز واللصق كاملة من الجينDSG4 للبحث عن الطفرة المسببة للمرض. النتيجة: ربط إنشاء التنميط الجيني في العوائل على الجين DSG4 في LAH1 الواقع على كروموسوم 18q21.1. الكشف عن تحليل تسلسل طفرة الحذف داخل الجين(EX5_8del)في الأفراد المصابين من كل العائلات الستة. الخلاصة: تحديد الطفرات المتكررة في ست عائلات باكستانية إضافية يعزز من الأدلة على أن هذا هي طفرة الأجداد التي تنتشر على نطاق واسع بين مختلف الجماعات العرقية الباكستانية. Abstract: Objectives: Localized autosomal recessive hypotrichosis is a non-syndromic human hair loss disorder, affecting scalp, eyebrows and eyelashes, and other parts of the body. Six consanguineous families with this form of hair loss disorder were investigated at both the clinical and molecular levels. Methods: Linkage in six families with twenty-one affected members was tested by genotyping microsatellite markers linked to autosomal recessive hypotrichosis loci including localized autosomal recessive hypotrichosis (LAH) 1, 2 and 3. Sequence analysis of the entire coding and splice sites of the gene DSG4 was performed to search for the disease-causing mutation. Results: Genotyping established linkage in families to the DSG4 gene at LAH1 locus on chromosome 18q21.1. Sequence analysis detected an intragenic deletion mutation (Ex5_8 del) in affected members of all six families. Conclusion: Identification of recurrent mutation in six additional Pakistani families strengthens the body of evidence that this is an ancestral mutation that is widespread among different Pakistani ethnic groups.